Free Energy Calculations using a Swarm‐Enhanced Sampling Molecular Dynamics Approach. Issue 15 (29th September 2015) - Burusco, Kepa K.; Bruce, Neil J.; Alibay, Irfan; Bryce, Richard A.
Abstract Free energy simulations are an established computational tool in modelling chemical change in the condensed phase. However, sampling of kinetically distinct substates remains a challenge to these approaches. As a route to addressing this, we link the methods of thermodynamic integration (TI) and swarm‐enhanced sampling molecular dynamics (sesMD), where simulation replicas interact cooperatively to aid transitions over energy barriers. We illustrate the approach by using alchemical alkane transformations in solution, comparing them with the multiple independent trajectory TI (IT‐TI) method. Free energy changes for transitions computed by using IT‐TI grew increasingly inaccurate as the intramolecular barrier was heightened. By contrast, swarm‐enhanced sampling TI (sesTI) calculations showed clear improvements in sampling efficiency, leading to more accurate computed free energy differences, even in the case of the highest barrier height. The sesTI approach, therefore, has potential in addressing chemical change in systems where conformations exist in slow exchange.